Initiation of the Dutch Inguinal Hernia Audit (DIHA): A survey on support for registration, obstacles, and possible areas of improvement - Richtje R. Meuzelaar; Floris P. J. den Hartog; Pieter J. Tanis; Anandi H. W. Schiphorst; Josephina P. J. Burgmans (International Journal of Abdominal Wall and Hernia Surgery)
BACKGROUND: Quality assessment and improvement of surgical procedures can be achieved by clinical audits that provide feedback on benchmarking of surgical outcomes. The Dutch Institute for Clinical Auditing (DICA) has successfully initiated registries with a clear impact on healthcare quality. Currently, there is no Dutch national inguinal hernia (IH) audit. This survey aimed to investigate the opinions of Dutch surgeons regarding the registration of IH care and explore potential obstacles in the implementation of a Dutch Inguinal Hernia Audit (DIHA). MATERIALS AND METHODS: A web-based survey was sent to all (>2,000) members of the Dutch Surgical Society, including surgeons and residents. RESULTS: Two-hundred sixty-seven respondents replied between April 14 and June 26, 2022 (hospital distribution: 36% small peripheral, 44% large peripheral, 11% academic, 2% specialized clinic). Almost two-thirds (60%) agreed that the quality of IH care should be improved. Similarly, nearly two-thirds (59%) answered that this improvement could be achieved through registration of surgical outcomes. Those opposed to registration stated fear of increased administrative burden and that the quality of care is already adequate. The majority of respondents agreed that chronic postoperative inguinal pain (CPIP; 81%) and recurrence rate (81%) should be used as quality indicators of IH surgery and registered as patient-reported outcome measures (PROMs). CONCLUSION: The majority of respondents agree that the quality of IH care could potentially be improved by implementing a national IH registry, with registration of CPIP and recurrence rate as quality indicators. Collecting these PROMs in a digital, automated format will facilitate successful implementation by minimizing administrative burden.